PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP PRESTASI KERJA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA KARYAWAN PT. BANK JATIM CABANG BONDOWOSO - Andreawan, Rama; Karnadi, Karnadi; Minullah, Minullah (Fakultas Ekonomi dan Bisnis, 2023)
This study aims (1) to determine the effect of leadership on job satisfaction (2) to determine the effect of the work environment on job satisfaction (3) to determine the effect of leadership on work performance (4) to determine the effect of work environment on work performance (5) to determine the effect of job satisfaction on work performance (6) to determine the effect of leadership on work performance through job satisfaction (7) to determine the effect of the work environment on work performance through job satisfaction. This research was analyzed through the Smart PLS 3.0 program. The results showed that the leadership variable had a significant effect on job satisfaction, work environment had a significant effect on job satisfaction, leadership had no significant effect on work performance, work environment had a significant effect on work performance, job satisfaction had a significant effect on work performance. The results of the indirect effect hypothesis test show that the variable Leadership on work performance through job satisfaction has a significant positive effect, work environment on work performance through job satisfaction has a positive but not significant effect.